The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acsptsci.2c00104
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Beneficial Effects of Ginger (Zingiber officinale Roscoe) in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder after Alzheimer’s disease (AD), and its pathogenesis remains obscure. Current treatment approaches mainly including levodopa and dopamine agonists provide symptomatic relief but fail to halt disease progression, and they are often accompanied by severe side effects. In this context, natural phytochemicals have received increasing attention as promising preventive or therapeutic candidates for PD, given their multitarget pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The raw materials of Moju are known to have pharmaceutical and nutraceutical activities. Ginger, the dried rhizome of the plant Zingiber officinale Roscoe (Zingiberaceae), has been utilized as a folk remedy for thousands of years and is a commonly used spice worldwide (Angelopoulou et al 2022). Some regulatory authorities classify ginger as a safe herbal supplement, and it has been used in both complementary and alternative medicine formulations for cold, fever, and headache management, as an appetite stimulant, and as an antiviral, antibacterial, choleretic, antidiarrheal, expectorant and antiemetic compound (Anh et al 2020;Mashhadi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The raw materials of Moju are known to have pharmaceutical and nutraceutical activities. Ginger, the dried rhizome of the plant Zingiber officinale Roscoe (Zingiberaceae), has been utilized as a folk remedy for thousands of years and is a commonly used spice worldwide (Angelopoulou et al 2022). Some regulatory authorities classify ginger as a safe herbal supplement, and it has been used in both complementary and alternative medicine formulations for cold, fever, and headache management, as an appetite stimulant, and as an antiviral, antibacterial, choleretic, antidiarrheal, expectorant and antiemetic compound (Anh et al 2020;Mashhadi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we screened similar compounds and selected two synthetic compounds (C10 and C14) for molecular dynamics simulations, in addition to one naturally occurring compound. There is much experimental evidence of ginger's beneficial effects on PD development 44 . Thus, we consider gingerol (the main pharmaceutically active compound in ginger) in our simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Ginger has been studied in these types of diseases. It has been observed that 6-shogaol inhibited some components of the inflammatory pathway, such as TNF-α, NO, COX-2, and iNOS, in patients with Parkinson’s disease [ 89 ]. In addition, it has been suggested that this compound may inhibit glial cell activation and reduce memory impairment in animal models of dementia [ 90 ], as well as exert a protective effect against amyloid-β in AD [ 91 ].…”
Section: Antioxidant Activity Of Zingiberaceae Familymentioning
confidence: 99%